Feet in Hell, Spirit in Heaven: Spiritual Transformation of Chinese Travelers on the Camino de Santiago - Zhang, Ke (Journal of religion and health, 2024)
The study aims to understand the precursors, catalysts, and dimensions of the spiritual transformation of Chinese travelers on the Camino de Santiago, a pilgrimage-tourist route in Spain. This research has adopted the theoretical framework of spiritual transformation by Pargament and his colleagues in collecting the transformative experience of Chinese Camino travelers reported in 139 blogs and stories. Thematic analysis is employed in analyzing the data. The study results show that Chinese travelers underwent spiritually transformative experiences, as observed in the changes in their relationship to themselves, others, nature, and the transcendent. These four dimensions are interconnected and experienced as something integrated with Chinese cultural and spiritual traditions. This study also explores the transculturality of spiritual experience, the important role of embodied engagement, and the critical and essential qualities of liminality in the transformative process on the Camino de Santiago.